Finance Decisions and Cash Flow Sensitivity : An Empirical Study of the Indian Industry - Roy, Dipen (Indian Journal of Finance, 2022)
To be effective in cash management, there is a necessity to quantify the influence of various finance functions on the cash accounts of the firms. This paper empirically measured the effects of finance functions on the cash account. The results revealed that the effect of cash flow on dividend decisions was statistically significant, while the effect of cash on capital budgeting and capital structure decisions was of limited relevance. Subsequent analysis unfolded that capital budgeting and capital structure decisions are inherently related; indeed, big size investments are linked with the mobilization of funds. While financing the investments, firms prioritized borrowing, and comparatively lower priority was given to mobilizing new equity capital. This observation confirmed the application of the pecking order hypothesis in the financing practice of Indian firms.